Explaining Consumers’ Intention for Traceable Pork regarding Animal Disease: The Role of Food Safety Concern, Risk Perception, Trust, and Habit - Huy Duc Dang; Giang Thanh Tran (International Journal of Food Science)
Purpose. The aim of this paper is to explain a consumers’ intention for traceable food in the context of the African Swine Fever (ASF) outbreak, in order to provide scientific knowledge for the government’s intervention to mitigate the perceived risk and to promote the development of traceable food. Methodology. This research employed an extended theory of planned behavior (TPB) model in predicting purchase intention/attitude toward traceable pork. The structural equation analysis (SEM) was used on a sample of 230 students in Vietnam. Findings. The current context of food safety issues, as well as animal disease outbreak, is beneficial to direct consumption toward traceable products. Heterogeneous impacts of trust were confirmed on how consumers perceived risks associated with the ASF outbreak. Consumers’ habits of shopping places and looking for the product origin incite the positive attitude toward traceable pork. Food safety concerns also promoted a positive purchase attitude. Originality/Value. The study’s objective is first to equip knowledge regarding the consumers’ intention toward traceable food under the impact of animal disease, particularly in the context of food safety issues in Vietnam. Extended knowledge promotes tailored policies to regain consumers’ confidence and facilitate the development of traceable food.